The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1101/2021.04.16.440241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Notch Intracellular Domain Plasmid Delivery via Poly(lactic-co-glycolic acid) Nanoparticles to Upregulate Notch Signaling

Abstract: Notch signaling is a highly conserved signaling system that is required for embryonic development and regeneration of organs. When the signal is lost, maldevelopment occurs and leads to a lethal state. Liposomes and retroviruses are most commonly used to deliver genetic material to cells. However, there are many drawbacks to these systems such as increased toxicity, nonspecific delivery, short half-life, and stability after formulation. We utilized the negatively charged and FDA approved polymer poly(lactic-co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 71 publications
(104 reference statements)
3
7
0
Order By: Relevance
“…Additionally, we loaded NICD plasmid to our PLGA nanoparticles to upregulate Notch signaling for the zebrafish in vivo experiment. From our previous work, we demonstrated that Tie2+Tie1 antibody conjugated PLGA nanoparticles successfully upregulated Notch related genes within the in vitro flow channel with HUVECs (Messerschmidt et al, 2021b). We also optimized NICD loaded PLGA nanoparticle concentration, 5 nL of 25 µg/mL, and injected at 48 hpf of zebrafish through the CCV.…”
Section: Upregulation Of Notch By Injecting Notch Intracellular Domai...mentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, we loaded NICD plasmid to our PLGA nanoparticles to upregulate Notch signaling for the zebrafish in vivo experiment. From our previous work, we demonstrated that Tie2+Tie1 antibody conjugated PLGA nanoparticles successfully upregulated Notch related genes within the in vitro flow channel with HUVECs (Messerschmidt et al, 2021b). We also optimized NICD loaded PLGA nanoparticle concentration, 5 nL of 25 µg/mL, and injected at 48 hpf of zebrafish through the CCV.…”
Section: Upregulation Of Notch By Injecting Notch Intracellular Domai...mentioning
confidence: 99%
“…TetO-FUW-NICD was a gift from Rudolf Jaenisch (Addgene plasmid #61540) (Cassady et al, 2014). Poly(D, L-lactide-coglycolic acid) nanoparticles (PLGA, 50:50, 55-65 kDa, Akina Inc., West Lafayette, IN, United States) were fabricated by a standard double emulsion method as previously described (Messerschmidt et al, 2021b). In brief, 250 µg of plasmid was diluted in 5% glucose solution to 200 µL which was then emulsified into 0.5 mL of 5% (w/v) PLGA solution in chloroform using a probe sonicator at 40W energy output for 15 s to form a primary water/oil emulsion.…”
Section: Nanoparticle Preparationmentioning
confidence: 99%
See 3 more Smart Citations